Dosimetry for ion beam radiotherapy - Karger, Christian; Jäkel, Oliver; Palmans, Hugo; Kanai, Tatsuaki (Physics in medicine and biology, 2010)
Recently, ion beam radiotherapy (including protons as well as heavier ions) gained considerable interest. Although ion beam radiotherapy requires dose prescription in terms of iso-effective dose (referring to an iso-effective photon dose), absorbed dose is still required as an operative quantity to control beam delivery, to characterize the beam dosimetrically and to verify dose delivery. This paper reviews current methods and standards to determine absorbed dose to water in ion beam radiotherapy, including (i) the detectors used to measure absorbed dose, (ii) dosimetry under reference conditions and (iii) dosimetry under non-reference conditions.